The Agrarian Question and the Neoliberal Rural Transformation in Latin America - Kay, Cristóbal (European Review of Latin American and Caribbean Studies, 2015)
Since the neoliberal turn in Latin America the rural economy and society has experienced a great transformation. Corporate capital and transnational agro-industries have taken hold of agriculture radically transforming the economic and social relations of production leading to the precarization and feminisation of rural labour as well as the intensification of work. Peasant farmers were further squeezed having to increasingly find off-farm incomes, largely through precarious wage labour activities, so as to make a living thereby furthering the process of proletarianization. The ‘new rurality’ and ‘territorial’ approaches tried to take account of these transformations but they are found wanting. Instead, a political economy view to the agrarian question is found more promising. A counter-movement to neoliberalism has emerged spearheaded by indigenous peoples and the rural poor, sometimes linked to the transnational peasant movement ‘Via Campesina’. Their main aim is to construct an alternative agrarian system based on ‘food sovereignty’ which is promising but also controversial. Resumen: La Cuestión Agraria y la Transformación Rural Neoliberal en Latinoamérica Desde el giro neoliberal en América Latina la economía y sociedad rural han experimentado una gran transformación. El capital corporativo y las agroindustrias transnacionales se han apoderado de la agricultura transformando radicalmente las relaciones económicas y sociales de producción que llevan a la precarización y feminización de la mano de obra rural, así como a la intensificación del trabajo. Los campesinos enfrentan condiciones cada vez más difíciles teniendo que buscar con mayor frecuencia ingresos fuera de la finca, principalmente a través de actividades salariales precarias, con el fin de ganarse la vida impulsando con ello el proceso de proletarización. Los enfoques de la ‘nueva ruralidad’ y ‘territoriales’ trataron de explicar estas transformaciones pero tienen limitaciones. En cambio, una visión desde la economía política sobre la cuestión agraria se estima más prometedora. Movimientos contestatarios del neoliberalismo han surgido encabezado por los pueblos indígenas y la población rural pobre, a veces vinculado al movimiento campesino transnacional ‘Vía Campesina’. Su principal objetivo es la construcción de un sistema agrario alternativo basado en la ‘soberanía alimentaria’, que es prometedor, pero también polémico.